REKONSTRUKSI CITRA PADA SUPER RESOLUSI MENGGUNAKAN INTERPOLASI BICUBIC - bagus hardiansyah; Aidil Primasetya Armin; Anton Breva Yunanda (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2019)
Digital image interpolation is important role in the geometric manipulation of a digital image. Interpolation is related to the process of mapping pixels, forward and reverse.Then this research will implementation of the bicubic interpolation method in the image process that is 16 pixel nearest neighborhood contained in the input image and generated a new pixel value with upscale and . Tests carried out on the type of RGB and images with BMP format with a variety of different image sizes. Tests with secondary data